Differences between homeless and non-homeless people in a matched sample referred for mental health reasons in police custody. (September 2020) - Hopkin, Gareth; Chaplin, Lucia; Slade, Karen; Craster, Laura; Valmaggia, Lucia; Samele, Chiara; Forrester, Andrew
Introduction: Homelessness has risen across high-income countries in the last decade, and in the United Kingdom, there has been a drastic increase in people living on the streets. Due to these increases, policy responses from public services are required to address the needs of this group. The risk factors for homelessness and conditions that this group live in mean they are at elevated risk of both mental health problems and contact with the criminal justice system. Despite this, there is little previous research on the homeless in police custody. Methods: Our study used a matched sample of homeless ( n  = 77) and non-homeless (n = 77) individuals to examine whether there were different needs across this group and whether the responses of a criminal justice mental health service differ for this group. This study is a secondary data analysis of a more extensive study. Results: Homeless and non-homeless detainees referred to the mental health service were broadly similar. However, differences in some variables show that homeless detainees had higher rates and frequency of substance misuse as well as some suggestion of more acute immediate need. Onward referrals were lower for homeless people, and it is not clear why this is the case. In addition, for those referred contact with services over time was reduced compared to the non-homeless group. Discussion: Our findings indicate that mental health services in police custody may need adaptations to ensure homeless individuals' higher level of need is addressed and that they receive appropriate care both during and after detention. Further quantitative and qualitative research is needed to confirm why responses differ and to assess what can be done to address this issue.